Cyborgization of Sport: the question of human naturalness - Jirasek, I. (Leipziger Sportwissenschaftliche Beiträge, 2013)
The basic problem of contemporary sport is the question if some boundary of growth exists. If such growth of records is possible ad infinitum, or if we have to crash on any boundaries. New terms as "transhumanism" or "posthuman- ism" denotative situation where the human personality try "to make better" his/her being through the techniques by overcrossing a horizon of (natural) humanity. When the human being stays at boundary of his/her possibilities at maximum achievement, he/she looks other ways leading to victory: doping and technique. However, both lead to dishonor of human naturalness, both squander the potential of authentic existence in sport framework and both lead to the cyborgization of sport.